Fine-structure deletion map and complementation analysis of the glnA-glnL-glnG region in Escherichia coli. - MacNeil, T (1982)
A total of 399 independent mutants of Escherichia coli were obtained which have point and insertion mutations in the glnA region. Mutants isolated included Gln- and Reg- strains (unable to utilize arginine as a nitrogen source). Mutations were mapped with 73 deletion-containing derivatives of a lambda gln phage. Complementation analysis was performed with lambda gln derivatives containing point mutations which conferred a Gln- or Reg- phenotype. Deletion mapping and complementation analysis assigned 104 mutations in 24 deletion intervals to glnA. Mutations in Reg- strains were assigned to two genes, glnL and glnG. glnL contained 131 mutations in 12 deletion intervals, and glnG contained 164 mutations in 10 deletion intervals. The gene order is glnA-glnL-glnG, transcribed from left to right. Polarity of insertion mutations indicates that glnL and glnG form from left to right. Polarity of insertion mutations indicates that glnL and glnG form an operon. Complementation analysis of glnA insertion mutations with glnL and glnG mutations showed polarity of glnA onto most glnL and glnG alleles, suggesting that transcription of glnA may proceed into the glnL-glnG operon. All mutations analyzed in glnA conferred a Gln- phenotype. However, we also found that over half of the Gln- strains isolated ater chemical mutagenesis contained point mutations in glnG. Mutants which synthesized a high level of glutamine synthetase in the presence of ammonia (GlnC phenotype) were selected as revertants of a strain with a Tn10 insertion in glnD and were mapped with chromosomal deletions. Results indicate that mutations in 12 and 15 examined strains clearly map outside of glnA, probably in glnL.